Micro‐scale inductorless maximum power point tracking DC–DC converter. Issue 8 (1st September 2013) - Grasso, Alfio Dario; Pennisi, Salvatore
Abstract : In this study, the authors propose a simple maximum power point tracking (MPPT) DC–DC converter amenable for micro‐scale photovoltaic applications. The solution avoids the use of inductors and exploits a charge pump as a voltage boost element. To take into account the temperature dependence of the MPP voltage, a passive temperature compensation circuit is also included. To validate the idea a prototype was realised with commercial off‐the‐shelf components. A system efficiency better than 83% for output power above 90 mW is obtained. The results show the viability of the proposed approach which could be further improved through a full custom integrated‐circuit design.